Emission estimates of HCFCs and HFCs in California from the 2010 CalNex study. Issue 4 (25th February 2013) - Barletta, Barbara; Carreras‐Sospedra, Marc; Cohan, Alex; Nissenson, Paul; Dabdub, Donald; Meinardi, Simone; Atlas, Elliot; Lueb, Rich; Holloway, John S.; Ryerson, Thomas B.; Pederson, James; VanCuren, Richard A.; et al.
Abstract : [1] The CalNex 2010 (California Research at the Nexus of Air Quality and Climate Change) study was designed to evaluate the chemical composition of air masses over key source regions in California. During May to June 2010, air samples were collected on board a National Oceanic and Atmospheric Administration (NOAA) WP‐3D aircraft over the South Coast Air Basin of California (SoCAB) and the Central Valley (CV). This paper analyzes six effective greenhouse gases—chlorodifluoromethane (HCFC‐22), 1, 1‐dichloro‐1‐fluoroethane (HCFC‐141b), 1‐chloro‐1, 1‐difluoroethane (HCFC‐142b), 2‐chloro‐1, 1, 1, 2‐tetrafluoroethane (HCFC‐124), 1, 1, 1, 2‐tetrafluoroethane (HFC‐134a), and 1, 1‐difluoroethane (HFC‐152a)—providing the most comprehensive characterization of chlorofluorocarbon (CFC) replacement compound emissions in California. Concentrations of measured HCFCs and HFCs are enhanced greatly throughout the SoCAB and CV, with highest levels observed in the SoCAB: 310 ± 92 pptv for HCFC‐22, 30.7 ± 18.6 pptv for HCFC‐141b, 22.9 ± 2.0 pptv for HCFC‐142b, 4.86 ± 2.56 pptv for HCFC‐124, 109 ± 46.4 pptv for HFC‐134a, and 91.2 ± 63.9 pptv for HFC‐152a. Annual emission rates are estimated for all six compounds in the SoCAB using the measured halocarbon to carbon monoxide (CO) mixing ratios and CO emissions inventories. Emission rates of 3.05 ± 0.70 Gg for HCFC‐22, 0.27 ± 0.07 Gg for HCFC‐141b, 0.06 ± 0.01 Gg for HCFC‐142b, 0.11 ± 0.03 Gg for HCFC‐124, 1.89 ± 0.43 Gg for HFC‐134a, and 1.94 ± 0.45 Gg for HFC‐152b for the year 2010 are calculated for the SoCAB. These emissions are extrapolated from the SoCAB region to the state of California using population data. Results from this study provide a baseline emission rate that will help future studies determine if HCFC and HFC mitigation strategies are successful. Key Points: HCFC and HFC emissions are calculated for the year 2010 for the SoCAB Emissions are extrapolated to the state of California Emissions are calculated using CalNex field measurements